Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-5 Division Properties of Exponents - Practice and Problem-Solving Exercises - Page 445: 78



Work Step by Step

=$\frac{(6a^{3})(8b^{4})}{(2a^{4}(36b^{-1})}$ =$\frac{48a^{3}b^{4}}{72a^{4}b^{-1}}$ =$\frac{48a^{3-3}b^{4+1}}{72a^{4-3}b^{-1+1}}$ =$\frac{48b^{5}}{72a}$ =$\frac{2b^{5}}{3a}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.